Cryptocurrencies: A political and a fiscal analysis - Rodrigues, Carlos (2019)
The existence of cryptocurrency a decade ago is an inescapable reality that at the moment generates a high financial influence at global level, the fact that obliges us to know and to study them. Our questions are essentially at three levels: their acceptance, or not, by the States in the face of the paper-money issued by their Central Banks and how the Private Banks react to this virtual currency created in particular; what actions have Tax Administrations at the global level faced with the wealth they generate and the financial values that move in the real economy. Our study is based on the doctrine that already exists, but mainly financial reports produced by central banks and private banking as well as by tax administrations. Finally, we present our conclusions on the current state of analysis and financial studies of the banking system and tax administrations and, of course, our opinion.